The positive impacts of using audiovisuals technology on the development of communicative skills in seventh-grade students in a public school in Loja city: Los impactos positivos del uso de la tecnología audiovisual en el desarrollo de las habilidades comunicativas de los estudiantes de séptimo grado de una escuela pública en la ciudad de Loja - Bravo Ludeña, Cristyan Paul; Chavez Reinoso, Sherlly Noemi; Valdez Vintimilla, Miryan Alexandra; Riera Hermida, Fernando Patricio (Boletín Científico Ideas y Voces, 2025)
Learning English presents significant challenges for students, requiring constant practice and innovative approaches beyond traditional methods. Research highlights that visual and audiovisual materials such as infographics, images, videos, podcasts, and educational games motivate learners, enhance comprehension, foster participation, and develop key skills by reducing anxiety and building confidence. However, their effectiveness depends on proper resource selection and alignment with specific language skills. Despite technological advances, barriers such as lack of resources, outdated teaching methods, overreliance on direct translation, and low motivation persist. In the context of rapid technological innovation, education has adapted by integrating multimedia tools to optimize teaching and learning, offering interactive, personalized, and globally connected experiences. This study focuses on public schools in Loja, Ecuador, particularly seventh-grade classrooms, to explore the use and effectiveness of audiovisual technology in improving students’ communicative skills.